Vanished : seven women magicians who simply disappeared - Hays, Anna (Bright Matter Books, 2025)
"Discover the amazing illustrated stories of seven women magicians who pulled off spectacular and death-defying illusions and acts, achieved global fame, and then simply...disappeared"-- Provided by publisher.